The Role of the Regional General Election Commission in Improving Political Participation of Bandung Society - Zindan Baynal Hubi; Ilham Aji Pangestu; Nursanda Rizki Adhari; Estu Supriyadi (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
The purpose of this study is to examine the role of the Bandung City Regional General Election Commission with its role in improving the political culture of community participants in the city of Bandung. This is mainly in facing the 2018 Bandung Mayor election. This research is a descriptive study that was analysed in several ways, namely data reduction, data presentation, conclusion drawing, and verification. The approach is done qualitatively, while the data collection technique is done by interview and observation. The participants selected in this study were the Regional General Election Commission of the City of Bandung (1 person) and the people of the City of Bandung (7 people). The results of this study indicate that the Bandung City Regional General Elections Commission in improving the political culture of participants with political education carried out various elements in the implementation of the Bandung City Regional Head election in 2018 it is known that the political participation of the community experienced significant growth and far exceeded the target set. The number of voter participants in the city of Bandung in the simultaneous regional head elections (Pilkada) in 2018 has increased compared to the last 5 (five) elections. The results also show that the increasing number of voter participants in the city of Bandung is inseparable from the cooperation of the Bandung City Regional Election Commission with various parties, both community organizations, policymakers, and other organizations in the city of Bandung. In the future, the political participation of the people of Bandung must always be maintained by involving various elements and innovations that adapt to changes and developments in society.